Reforming of Professional Translator Training in Germany on the Basis of Bologna Process - Natalia Levyts’ka (Pedagogical Discourse, 2012)
The article deals with the peculiarities of reforming of professional translator training under the conditions of Bologna Process, and training programs for translators in the Universities of Germany are analyzed